100TH ANNIVERSARY OF THE BIRTH OF V L GINZBURG. REVIEWS OF TOPICAL PROBLEMS : Double plasma resonance and its manifestations in radio astronomy. (28th December 2016) - Zheleznyakov, V V; Zlotnik, E Ya; Zaitsev, V V; Shaposhnikov, V E
Abstract: The double plasma resonance (DPR) effect is the phenomenon of a sharply increased instability of plasma waves in a magnetized plasma when the upper hybrid frequency coincides with the cyclotron harmonic frequency. A radiation mechanism associated with this effect provides an explanation for the origin of the 'zebra pattern' in radio spectra of the Sun, Jupiter, and the Crab pulsar. The diversity of these astronomical objects and the successful interpretation of their spectra in terms of the DPR effect point to the universal nature of this phenomenon and suggest that the same radiation mechanism can operate under a variety of astronomical conditions.